Call Night - Aaronson, Nicole Leigh (Ars Medica, 2017)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This work is a piece of fiction inspired by some of my more interesting nights on call as an otolaryngology resident. I hope to share this piece to help discuss some of the issues in caring for individuals who cannot care for themselves, coping with emergency situations, and what it really means to take in-house hospital call as a resident.